Linkage Mapping and Genome-Wide Association Studies of the Rf Gene Cluster in Sunflower (Helianthus annuus L.) and Their Distribution in World Sunflower Collections - Talukder, Zahirul I.; Ma, Guojia; Hulke, Brent S.; Jan, Chao-Chien; Qi, Lili (Frontiers in Genetics, 2019)
Commercial hybrid seed production in sunflower currently relies on a single cytoplasmic male sterility (CMS) source, PET1 and the major fertility restoration gene, Rf1, leaving the crop highly vulnerable to issues with genetic bottlenecks. Therefore, having multiple CMS/Rf systems is important for sustainable sunflower production. Here, we report the identification of a new fertility restoration gene, Rf7, which is tightly linked to a new downy mildew (DM) resistance gene, Pl34, in the USDA sunflower inbred line, RHA 428. The Rf7 gene was genetically mapped to an interval of 0.6 cM on the lower end of linkage group (LG) 13, while Pl34 was mapped 2.1 cM proximal to the Rf7. Both the genes are located in a cluster of Rf and Pl genes. To gain further insights into the distribution of Rf genes in the sunflower breeding lines, we used a genome-wide association study (GWAS) approach to identify markers associated with the fertility restoration trait in a panel of 333 sunflower lines genotyped with 8,723 single nucleotide polymorphism (SNP) markers. Twenty-four SNP markers on the lower end of LG13 spanning a genomic region of 2.47 cM were significantly associated with the trait. The significant markers were surveyed in a world collection panel of 548 sunflower lines and validated to be associated with the Rf1 gene. The SNP haplotypes for the Rf1 gene are different from Rf5 and the Rf7gene located in the Rf gene cluster on LG13. The SNP and SSR markers tightly flanking the Rf7 gene and the Pl34 gene would benefit the sunflower breeders in facilitating marker assisted selection (MAS) of Rf and Pl genes.